PERSESI PENGUSAHA MIKRO TERHADAP ADANYA RUANG TERBUKA HIJAU (RTH) DI KOTA PONTIANAK KALIMANTAN BARAT - Rio Laksamana (Jurnal Ekonomi Integra, 2020)
The regional government of Pontianak City in West Kalimantan is working to increase and improve the quality of green space to 30% in accordance with the provisions of Law no. 26 of 2007 concerning spatial planning. The purpose of this study is to find out how micro entrepreneurs' perceptions of the existence of green open space (RTH) in Pontianak City, West Kalimantan. The research method used in this study is a descriptive survey method with a qualitative approach to interview techniques. Samples were 50 micro entrepreneurs who were around the open green space. The result is the perception of micro entrepreneurs in managing green open space in general is very positive